P025 Colonic rather than ileal expression of ITGA4/ITGB7 correlates with local intestinal inflammation in IBD. (30th January 2023) - Csomor, E; Gehrmann, U; Monkley, S; Tian, S; Cairns, J; Angermann, B; Khan, E; Nys, J; Marks, D
Abstract: Background: Lymphocyte trafficking to the inflamed gut is one of the hallmarks of Inflammatory Bowel Disease (IBD) pathology. Integrin a4b7 and its ligand MADCAM1 play an important role in targeting immune cells in the bloodstream to mucosal tissues and blocking this pathway using the anti-a4b7 monoclonal antibody Vedolizumab (VDZ) proved to be an effective treatment in IBD. However, VDZ is most efficient in treatment of Ulcerative Colitis (UC) and of colonic rather than ileal Crohn's Disease (CD), for which the reasons have not been completely understood. Here we sought to compare the expression of ITGA4, ITGB7 and MADCAM1 in gut tissue biopsies from small and large bowel with respect to the underlying severity of tissue inflammation. Methods: Differential gene expression analysis was conducted using bulk RNA Sequencing data generated from gut tissue biopsies of the large and small intestine of 611 CD and 315 UC patients enrolled in a multicentred longitudinal Study of a Prospective Adult Research Cohort with IBD (SPARC IBD) obtained from the IBD Plexus program of the Crohn's and Colitis Foundation. Gene expression levels of ITGA4, ITGB7 and MADCAM1 were compared across ileal, colonic and rectal segments of the intestine and data were then linked to available measures of local inflammation. Results: ITGA4, ITGB7 and MADCAM1 were expressed at comparable levels in large vs small bowel biopsies. Expression of MADCAM1 was significantly increased in both ileal and colonic biopsies from patients with moderate to severe CD based on segmental or composite endoscopy score (SES-CD) across all bowel segments. Expression of both ITGA4 and ITGB7 was similarly increased in colonic biopsies of moderate/severe CD patients, whereas only minor changes were observed for both genes in ileal biopsies. Similar findings were obtained from UC patients, where expression of MADCAM1 was significantly increased in inflamed or ulcerated biopsies from both sigmoid colon and cecum as compared to normal appearing biopsies. Expression of ITGA4 and ITGB7 was only increased in inflamed/ulcerated biopsies of the sigmoid colon but not the cecum and correlated with the modified Mayo endoscopic score (MMES). Conclusion: Our analysis suggests that influx of leukocytes to inflamed tissue via ITGA4/ITGB7 and MADCAM1 interactions is more common in the distal colon compared to proximal colon or ileum. This provides a possible mechanistic explanation as to why VDZ is most effective in patients with colonic IBD. Further work is needed to understand the differential regulation of cell trafficking to different regions of the gut.